Molecular Tools in Buffalo’s Characterization: Practical Applications. A Review - Reinosa, Odalys Uffo; Abad, Atzel Acosta (Journal of Buffalo Science, 2012)
The utility of the techniques of analysis concerning DNA is clear and a review of the main applications of the molecular tools in the genetic characterization of buffalo populations is done.